Efficient use of raw materials in textile enterprises and ensuring product quality - Umida Nurillaevna Yusupalieva (Open Science LLC, 2021)
The article examines the experience of using raw materials by enterprises operating in the Republic and also analyzed the above studies to study the preparation of the optimal sorting of the selected raw materials.